Relearning Data in Education: Inspiriting Truth and Reconciliation Teacher Education as an Emerging and Expanding Relational Field - Phillips, Patrick (Université d'Ottawa / University of Ottawa, 2025)
This thesis-by-article documents my psychical, physical, indeed spiritual doctoral studies journey to understand and make felt how we (or at least me, as a white Canadian citizen) as scholars and educators might fully attend to the relational implications of relationality in our work, including how we might honour the relationality of our data from review and theorization, collection, analysis, and re/presentation through our knowledge dissemination as archived and taught. Inspired by the relational implications of the Truth and Reconciliation Commission (TRC) and its calls for teacher education praxes, my doctoral work became necessarily a multi-layered methodological project as well as an arts-based knowledge dissemination prototyping project. I share three main manuscripts: 1) a relational literature review titled and published as The transeunt listener: Towards futurities of re-learning in truth and reconciliation curriculum and teacher education; 2) a methodological frameworks treatise titled Relational lacunae and (re)turning: Towards an inspirited relational research methodology for curriculum studies and kindred futurities; and 3) a report on the methods and findings of my dissertation research titled Relearning data in education: An arts-based inspiriting of Truth and Reconciliation teacher education. After introducing this dissertation document in Chapter 1, in Chapter 2 I share what I have termed the practice of a transeunt listener, or myself as a reader who engages reading while open to and experiences subjective and intersubjective transformation through reading the words of authors as an opportunity to both physically and psychically move through and listen for the complexly relational hopes of those other than myself. Through my literature review and listening to the data of my research participants, all influential scholars of TRC-responsive education (n=3 Indigenous and n=2 non-Indigenous), I realized a key gap in truth and reconciliation re/presentations: spirit. I follow my central methodological call from Chapter 2 in Chapter 3, theorizing towards the possibility of a robust and multivalent discourse of spirit, what (or whom) I offer is the vital solvent and resolvent between notions of relationality as a distinct yet commensurate formation between Indigenous and non-Indigenous worldviews that challenges theorists to reimagine what they mean by the word 'relationality.' I offer that spirit is not only what animates all life and relationships but is also a real, animate more-than-human relative constitutive of ourselves and our data, and so call on all scholars of complex relational topics to begin seeking spirit in/as data rather than continuing its elision in theory, re/presentation of research, and practice. In Chapter 4, I share my findings and preliminary considerations of the re/presentational and practical implications of researching and teaching towards relearning spirit as data and curricular kin. Pragmatically for my deposited dissertation, this takes the form of a richly visualized, arts-based report on the methods and findings of my dissertation research including my preliminary process work with Jordyn Hendricks, a Two-Spirit and Red River Métis artist with ties to the St. Laurent and The Pas regions of what is now Manitoba. In Chapter 5, I conclude my dissertation research writing with present and future implications, and hopes, for seeking spirit in education.
Keywords: methodology; relationality; ethical relationality; kinship relationality; truth and reconciliation; truth; reconciliation; curriculum; curriculum studies; education; teacher education; arts-based; kinship; visualization; materialization; data; spirit; inspiriting; Indigenous education; decolonization; settler colonialism; colonialism; non-disciplinary; aesthetics; aesthetic politics; futurity; future dreaming; arts-based methods; relearning; unlearning; emerging fields; embodied scholarship; spiritual; spirituality; intercultural education; international education; democracy; anti-racism; anti-oppression; ecological kinship; research methodology; research methods; alternative dissemination; intersubjectivity; more-than-human; representation; cultural studies; aesthetico-political; complexity; ecojustice; social justice; Indigenous resurgence; Indigenization; reparative curriculum; trasnformative pedagogy; collaborative research; decolonial research; anti-colonial research; worldview; research design; curriculum design; relational field; ethics; ethics of care; relational ethics; psychical curriculum; metaphysics; practical ethics; spiritual ethics; data portraiture; creation-centred literacy; pedagogy; arts-based pedagogy; interdisciplinarity; transdisciplinarity; decolonial pedagogy; praxis; bridging worldviews; ethics of education; philosophy of education